Conservative transformation of education in Turkey (1980-2012) : policy processes and power alliances - Canlı, Gamze. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2023., 2023)
This research explores the role of several civil conservative- Islamist organizations and their relational networks in the conservative transformation of educational policy in Turkey between 1980 and 2012. It examines how the pow-er bloc of the conservative Islamist organizations over the educational policy has been historically and relationally constituted and shaped. It analyzes the modalities and motivations that bring these constellations together, the shaping of their hegemony projects and their power building strategies, and the relational and historical dynamics that empower them to orient educational policy field. The research focuses on four major periods of educational policy between the years 1980 and 2012: The ideological designation of the education system with the Turkish-Islamic Synthesis in the 1980s, the process of the eight years of compulsory education reform during the 1990s, the neoliberal-populist regime of educational policies during the 2000s, the implementation of the 4+4+4 compulsory education model in 2012. Semi-structured inter-views and textual analysis are utilized as qualitative research methods. The research argues that conservative transformation of educational policy is not a monolithic and linear process defined with the steadily rising influence and power of the conservative- Islamist actors. Conservatism in edu-cation has rather been a product of the changing modalities and dynamics of alliance building among diverse agents, within which the currently powerful conservative-Islamist groups develop different power building strategies. The research claims that the main power resource of these groups is their interorganizational networks and expanding social capital across civil and political platforms. The proactivity for the advocacy for religious education, on the other hand, functions to forge a common ground that unities them as a conservative-Islamist power bloc.
Keywords: Education and state -- Turkey -- 20th century.; Education -- Aims and objectives -- Tuerkey.; Conservatives -- Turkey.